FAKTOR PENYEBAB SISWA TIDAK MENCAPAI KKM PADA MATA PELAJARAN MATEMATIKA - Sudarto Sudarto; Ilham Ilham; Muhammad Idris Jafar (Sekolah Tinggi Pariwisata Mataram, 2023)
This research is a qualitative research that aims to describe the factors causing the Fifth Grade students do not achieve the KKM in Mathematics at UPTD SDN 77 Mahaka. The subjects of this study were the fifth grade students, parents of the fifth grade students and UPTD teachers at SDN 77 Mahaka. Collecting data using observation, interviews and documentation. Data analysis techniques namely data reduction, data presentation, and drawing conclusions. The results and conclusions of the study indicate that the factors causing the fifth grade students do not reach the KKM in mathematics include internal factors and external factors. Where internal factors include: students consider the mathematics is difficult, students are less interested in learning the mathematics; students lack concentration when learning mathematics; students' motivation to learn mathematics is low; and the unhealthy of the student body condition. External factors include: the use of media or visual aids that are less than the teacher's; and students' family situations that are less in supporting.